2015
DOI: 10.1016/j.devcel.2015.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Direct Microtubule-Binding by Myosin-10 Orients Centrosomes toward Retraction Fibers and Subcortical Actin Clouds

Abstract: SUMMARY Positioning of centrosomes is vital for cell division and development. In metazoan cells, spindle positioning is controlled by a dynamic pool of subcortical actin that organizes in response to the position of retraction fibers. These actin “clouds” are proposed to generate pulling forces on centrosomes and mediate spindle orientation. However, the motors that pull astral microtubules toward these actin structures are not known. Here, we report that the unconventional myosin, Myo10, couples actin-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
120
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(133 citation statements)
references
References 50 publications
13
120
0
Order By: Relevance
“…In the epithelium of the developing frog embryo, Myo10 depletion results in a suite of mitotic spindle phenotypes including abnormal spindle movements, spindle elongation, and pole fragmentation (Woolner et al 2008). Further, several studies have demonstrated that perturbing Myo10 function in cultured cells (two and three-dimensional cultures) and intact epithelial tissues causes a loss of normal spindle positioning/orientation (Kwon et al 2015; Liu et al 2012; Toyoshima and Nishida 2007; Woolner and Papalopulu 2012). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the epithelium of the developing frog embryo, Myo10 depletion results in a suite of mitotic spindle phenotypes including abnormal spindle movements, spindle elongation, and pole fragmentation (Woolner et al 2008). Further, several studies have demonstrated that perturbing Myo10 function in cultured cells (two and three-dimensional cultures) and intact epithelial tissues causes a loss of normal spindle positioning/orientation (Kwon et al 2015; Liu et al 2012; Toyoshima and Nishida 2007; Woolner and Papalopulu 2012). …”
Section: Introductionmentioning
confidence: 99%
“…The MyTH4 domain is of particular interest in examining Myo10’s spindle functions, as this domain contains a patch of basic amino acids that mediates binding to microtubules via electrostatic interaction with the acidic tails of tubulin (Hirano et al 2011; Kwon et al 2015). As such, it is reasonable to expect that the MyTH4 domain would form the basis for Myo10’s spindle localization (Woolner et al 2008), although this has yet to be directly demonstrated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, at least part of Myo10’s contribution to mitosis is somehow mediated through control of cell cycle progression, as the depletion of Myo10 (Woolner et al, 2008) or expression of its isolated “Myth4” domain (Sandquist, Larson, & Hine, 2016) greatly slows the metaphase–anaphase transition. While it is not yet known how widely required Myo10 is for cell division in other systems, Myo10 has been implicated in spindle formation in Xenopus and mammalian meiosis (Brieño-Enríquez et al, 2017; Weber et al, 2004), and in spindle stability and dynamics in several cultured cell types (Chan, Hsu, Liu, Lai, & Chen, 2014; Iwano et al, 2015; Kwon, Bagonis, Danuser, & Pellman, 2015; Kwon et al, 2008; Toyoshima & Nishida, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, conservation of these surface residues among different Myo10 sequences, from the evolutionarily distant Choanoflagallate Monosiga brevicollis to human (Fig. 3A), suggests that the interaction with MTs [which is crucial in vertebrates for orienting the mitotic spindle by anchoring it to the cortex (11,32)] is likely to be an ancient property of Myo10 myosins.…”
Section: Conservation and Divergence In The Myth4 Domain Of Evolutionmentioning
confidence: 99%